2009
DOI: 10.1086/596658
|View full text |Cite
|
Sign up to set email alerts
|

Role Played by Human Mannose-Binding Lectin Polymorphisms in Pulmonary Tuberculosis

Abstract: This study supports the conclusion that MBL can protect or predispose the host to tuberculosis, depending on the host's haplotype pair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 44 publications
1
33
0
1
Order By: Relevance
“…[16][17][18] Genetic stratification, 21-24 low statistical power 18 and multiple testing without Bonferroni correction [20][21][22][23][24][25] are frequently indicated as sources of false-positive findings. It is therefore relevant to discuss how each of these potential artifacts was controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] Genetic stratification, 21-24 low statistical power 18 and multiple testing without Bonferroni correction [20][21][22][23][24][25] are frequently indicated as sources of false-positive findings. It is therefore relevant to discuss how each of these potential artifacts was controlled.…”
Section: Discussionmentioning
confidence: 99%
“…23 Comparison of the results from the two studies provides vivid evidence of how two haplotype pairs, both protective, can differ significantly in penetrance: whereas only 2 out of 278 patients displayed the protective haplotype pair MBL-HYA/HYA, 20 many more (38 out of 305) of the same patients displayed the protective haplotype pair V-ATPase 13/24 ( Table 5). The difference in penetrance might reflect intrinsic differences between the two haplotype pairs or differences in the way host (background genes, prior immunity) and microbial factors (M. tuberculosis strain) influence the two haplotype pairs.…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies are the primary component of humoral immunity [15] and aid in the development of an opsonized response [16]. Numerous studies investigated the role of antibodies against Mtb infection [17][18][19] and documented antigens recognized by antibodies included the Ag85 complex [15,[20][21][22], lipoarabinomannan (LAM) [23,24], arabinomannan (ARM) [18], the 6 kDa early secretory antigen target (ESAT-6) and the 10 kDa culture filtrate protein (CFP-10) [19]. The memory B cell response in BCG-vaccinated individuals have been shown to be present even 45 years following vaccination [19].…”
Section: The Immune Response To Mtbmentioning
confidence: 99%
“…Certain classes of antibodies have specificity for extracellular Mtb antigens, as do mannose-binding lectins [24,27] that recognize the LAM and ARM molecules on the Mtb surface. Both of these opsonins activate the third component of complement and the complex of Mtb-opsosin-C3 binds via C3 to its receptor (CR3) on phagocytes [20,28].…”
Section: The Immune Response To Mtbmentioning
confidence: 99%
“…18,19 in contrast, results from other studies have indicated that protection against the disease is associated with high levels of MBL. 20,21 the genes responsible for the variations in human susceptibility and resistance to tB have yet to be identified. in an effort to better understand the mechanisms that are involved in mycobacterial infection, we evaluated 3 of the 5 mbl-2 polymorphisms as possible risk factors for mycobacterial infection in a case-controlled setting.…”
mentioning
confidence: 99%